Computer Literacy Skills and Institutional Factors as Determinants of Electronic Resources Use by Postgraduates in a Nigerian University - Ajegbomogun, Fredrick Olatunji; Achigbue, Esther; Diyaolu, Basirat O. (Ghana Library Journal, 2022)
The purpose of this study was to investigate the level of computer literacy skills and institutional factors influencing postgraduates’ use of Electronic Resources (ERs) at the Federal University of Agriculture, Abeokuta. The Yamane formula for calculating sample size was used to determine 312 postgraduate students who represented the sample size of the study. A simple random sampling technique was used to administer the structured questionnaire, while the SPSS was also used to analyze the data. The majority (92.3%) of the postgraduates in FUNAAB have high computer literacy skills with skills in internet usage, word processing applications (81.6%) and spreadsheet applications (75.5%). They use e-prints, e-journals (76.9%), AGORA and HINARI (67.0%) often, but EBSCOHOST had low usage (34.6%). However, inadequate space, insufficient computer systems and inadequate ICT training programmes were institutional factors identified as challenges to using ERs by the respondents. The study established that computer literacy skills do not affect the use of ERs by postgraduates in FUNAAB. It was recommended that library management should work towards the expansion of the e-library unit as this will provide enough space to accommodate a large number of students using the library and improve the use of ERs by postgraduates.